Perencanaan Saluran Terbuka Drainase Area Penambangan Komoditas Feldspar di Kecamatan Gandusari - Muhammad Fairuz Akmal; Tuhu Agung Rachmanto (International Forum of Researchers and Lecturers, 2024)
PT MAS operates in the mining sector, extracting white rocks or feldspar from steep and rugged slopes. Inadequate drainage systems pose significant challenges, such as floods, erosion, and landslides, emphasizing the critical role of effective drainage in mining activities. The designed drainage system incorporates trapezoidal open channels at the mining steps' base. Before reaching natural water bodies, mining water is directed to sedimentation ponds to settle sediments. This research, an experimental study correlating theory with field data, begins with a literature review on open channel drainage theories in mining areas. Data collection includes location specifics, mining area dimensions, rainfall, and runoff coefficients. Manning equation calculations determine planned open channel dimensions, with a bottom width of 0.45 m, flow depth of 0.39 m, freeboard height of 0.097 m, water surface width of 0.9 m, and a slope angle of 60⁰. The research aims to contribute insights for the development and management of open channel drainage systems in mining areas.